Effect Of Problem-Based Learning Supported By Media Edukatıf On İmproving Students' Understanding And Solving Matter Problems Of Rotation And Revolution Of The Earth - Sofia, Lucky Ermina; Anggoro, Subuh; Firmasyah, Juli (Jurnal Elementaria Edukasia, 2024)
This research is motivated by the importance of improving students' understanding of concepts and problem solving skills in the material of rotation and revolution of the Earth, which is often difficult to understand because it requires clear visualisation. Problem Based Learning (PBL) supported by educational media is expected to help students to understand the concept more deeply and to improve their problem solving skills. The purpose of this study was to analyse the effect of using PBL with the help of educational media to improve students' understanding and their ability to solve problems about material rotation and revolution of the earth.This study uses experimental methods with pre-experimental design because there are 3 stages, namely pre-test, treatment and post-test. The samples were selected using purposive sampling technique, the total number of samples used in this study was 40 students of Karang Padak Primary School. Data were collected through concept comprehension tests and problem solving ability tests, then analysed using statistical tests.The results showed that students who studied with PBL approach supported by educational media experienced a significant increase in concept comprehension. In addition, the problem-solving skills of the students in the experimental group also improved significantly. These findings indicate that PBL supported by educational media is effective in improving students' understanding and skills in learning the concept of rotation and revolution of the Earth. Conclusion The application of PBL supported by educational media can have a positive impact on improving students' understanding of concepts and problem solving skills on the rotation and revolution of the Earth.